RELATIONSHIP BETWEEN SAFETY CULTURE AND THE SAFETY CLIMATE, SAFETY BEHAVIOR AND SAFETY MANAGEMENT - Dian Palupi Restuputri; M Syahban Giraldi; Shanty Kusuma Dewi; Ilyas Masudin; Uci Yuliati (Majalah Ilmiah Pengkajian Industri, 2021)
This article aims to measure the application of occupational safety and health using Cooper's Reciprocal Safety Culture Model and Confirmatory Factor Analysis method.  The objective function of this article is to find out the aspects of safety culture that have been implemented by companies. A questionnaire was circulated to staff on the company's production floor as part of this study. The results of the questionnaire recapitulation were then analyzed using the confirmatory factor analysis method. Based on the score calculation results and the category determination build on the questionnaire scores on each dimension of the safety culture applied to the Steel Company, the safety climate value of 55.58 is obtained, which is on a 'quite good' scale. The safety behaviour value of 44, 89 is included on a 'quite good' scale, the safety management system value of 22.04 is on a 'poor' scale, and the safety culture value of 40.83 is on the 'quite good' scale. With these results, it is essential to make improvements to the safety culture in the company, especially in the dimensions of the safety management system, which is on the 'quite good' scale.